2015
DOI: 10.1007/s10854-015-2761-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rf power on the properties of magnetron sputtered CeO2 thin films

Abstract: Cerium oxide (CeO 2 ) thin films were prepared by rf magnetron sputtering (PVD) technique onto glass substrates at a pressure of 3 9 10 -4 mbar of Ar ? atmosphere. The thickness of deposited CeO 2 films ranges from 380 to 590 nm. X-ray diffraction studies on the films showed that the films are polycrystalline in nature. The crystallite size (D), dislocation density (d) and micro-strain (e) were evaluated from XRD patterns. The obtained micro-strain and dislocation density of the films were found to be *10 -3 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…This is attributed to poor crystallinity and large disorder in the films [19]. It is reported that CeO 2 films with smaller crystallite show poorer luminescence, which is attributed to non radiative relaxation through surface states [36].…”
Section: Room Temperature Pl Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…This is attributed to poor crystallinity and large disorder in the films [19]. It is reported that CeO 2 films with smaller crystallite show poorer luminescence, which is attributed to non radiative relaxation through surface states [36].…”
Section: Room Temperature Pl Studiesmentioning
confidence: 99%
“…Figure 7 These Raman active modes are attributed to a symmetrical stretching mode of Ce-8O vibrational unit, and therefore, they are very sensitive to any disorder in oxygen sub lattice that resulted from thermal, doping, or grain size [19,[38][39][40][41]. The effect of microstructure of CeO 2 on the shape of the Raman spectra was observed by broadening the line and by increasing its asymmetry, which are attributed to the reduction in phonon lifetime in the nanocrystalline regime [42][43][44].…”
Section: Raman Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…As observed in Figure B(f), the matching IR spectra gave a similar absorption band around 1380 cm ‐1 assigning to the characteristic vibration mode of CeO 2. In Figure A(f), after the H‐CLACF MCs were calcined at 550 °C (H‐CLACF‐550), the amorphous La 2 O 3 crystallites still remains amorphous, not appearing crystal structure transformation . The peak at 33.2° corresponding to the (104) crystal planes of a‐Fe 2 O 3 confirms that a small portion of Fe 3 O 4 transfers into the α‐Fe 2 O 3 .…”
Section: Resultsmentioning
confidence: 82%
“…The details of the target preparation and coating procedures are described elsewhere [6]. Argon was used as the plasma generation gas.…”
Section: Experimental Procedurementioning
confidence: 99%